Characterization of autonomic symptom burden in long COVID: A global survey of 2,314 adults - Larsen, Nicholas W.; Stiles, Lauren E.; Shaik, Ruba; Schneider, Logan; Muppidi, Srikanth; Tsui, Cheuk To; Geng, Linda N.; Bonilla, Hector; Miglis, Mitchell G. (Frontiers in Neurology, 2022)
Background: Autonomic dysfunction is a known complication of post-acute sequelae of SARS-CoV-2 (PASC)/long COVID, however prevalence and severity rates are unknown. Objective: To assess the frequency, severity, and risk factors of autonomic dysfunction in PASC, and to determine whether severity of acute SARS-CoV-2 infection is associated with severity of autonomic dysfunction. Design: Cross-sectional online survey of adults with PASC recruited through long COVID support groups between October 2020 and August 2021. Participants: 2413 adults aged 18 to 64 years with PASC including patients who had a confirmed positive test for COVID-19 and participants who were diagnosed with COVID-19 based on clinical symptoms alone. Main measures: The main outcome measure was the total Composite Autonomic Symptom 31 (COMPASS-31) score, used to assess global autonomic dysfunction. Test-positive hospitalized vs. test-positive non-hospitalized participants were compared to determine whether the severity of acute SARS-CoV-2 infection affected the severity autonomic dysfunction. Key Results: Sixty-six percent of PASC patients had a COMPASS-31 score >20, suggestive of moderate to severe autonomic dysfunction. COMPASS-31 scores did not differ between test-confirmed hospitalized and test-confirmed non-hospitalized participants (28.95 [15.62, 46.60] vs 26.4 [13.75, 42.10]; p=0.06). Conclusions: Moderate to severe autonomic dysfunction was seen in all PASC patients in our study, independent of hospitalization status, suggesting that autonomic dysfunction is highly prevalent in the PASC population and independent of the severity of acute COVID-19 illness.